(3LhGgQ GdHMhQ hhbGFY GdCehQ hYLGFH GdOghQ hCNHGQ GdOjGQ GdeUQjIs - (3eMehO Hf CMeO Hf ehSi Hf CMeO, CHh eMeO, HOQ GdOjf GdYjfj , J (B855 (3g` s
(3ChdgG (B:s
(3CYde CjgG GdSGeY habfi Gddg hEjGc dWGYJg Cf eUQ cGfJ ef CLd GdHdGO s
(3BNQgG (B:s
(3Ke Jhdi WheGf HGj GHf CNj GdZhQi Ke Sdje TGg Ke hdOg SdjeGf , hGddg JYGdi CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3aj CNHGQ GdOjGQ GdeUQjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B150s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B336 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B574 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B143 s
Keywords: (3GdJGQjNs